2008
DOI: 10.1002/jbt.20215
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic phosphate stimulates the toxic effects of Tl+ in rat liver mitochondria

Abstract: We studied action of inorganic phosphate (P(i)) on toxic effects of Tl+ in isolated rat liver mitochondria. This is a convenient model to study the toxicity of heavy metals. P(i) markedly retarded contraction of energized mitochondria swollen in the TlNO3 medium and even stronger stimulated swelling and state 4 of succinate-energized mitochondria in the TlNO3 medium. A valinomycin-induced decrease of K+-diffusion potential was also accelerated by Tl+ in the presence of P(i). The mitochondrial permeability tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
3
9
0
Order By: Relevance
“…These findings can be explained by the fact that DTT reduces Cd 2+ inhibition of respiratory enzymes that are not affected by Tl + . Conversely, we postulated earlier that a more potent decrease in state 4, state 3, and DNP‐stimulated respiration of RLM in nitrate salt media containing TlNO 3 and Ca 2+ was due to massive mitochondrial swelling (Figures and ). The effects of cations on respiration and swelling of energized RLM in nitrate media increased in the order of Ca 2+ < Tl + + Ca 2+ < Cd 2+ < Cd 2+ + Ca 2+ .…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…These findings can be explained by the fact that DTT reduces Cd 2+ inhibition of respiratory enzymes that are not affected by Tl + . Conversely, we postulated earlier that a more potent decrease in state 4, state 3, and DNP‐stimulated respiration of RLM in nitrate salt media containing TlNO 3 and Ca 2+ was due to massive mitochondrial swelling (Figures and ). The effects of cations on respiration and swelling of energized RLM in nitrate media increased in the order of Ca 2+ < Tl + + Ca 2+ < Cd 2+ < Cd 2+ + Ca 2+ .…”
Section: Discussionmentioning
confidence: 85%
“…We have earlier suggested that the interaction of Tl + with MSG may be one of the causes of thallium toxicity . The interaction would decrease the content of IMM SH groups, similar to the effects of PhAsO or Ag + . Conversely, we found an increase in IMM content in experiments with RLM, incubated and frozen in media containing TlNO 3 (Figures and , panels A–D).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations